Pesan yang Terkandung dalam Tari Bawang Merah dan Bawang Putih - Sari, Nadira Puspita (PPSDP Undergraduate Journal of Educational Sciences, 2025)
The dance drama “Bawang Merah dan Bawang Putih” is a cultural heritage rich in moral values. This study aims to reveal the moral messages contained in the dance drama through an in-depth analysis of movement, costumes, music, and background. The research findings show that this dance drama conveys moral messages relevant to human life, such as the importance of kindness, patience, and justice. Additionally, the study identifies how these moral messages are effectively communicated through body language and visual symbols.